The target and impact of Kt/V for Asian ESRD patients on haemodialysis - Mohamad Nor, Fariz Safhan; Hamzah, Mohd Hazlan; Seman, Mohd Ramli; MK, Ahmad; Chan, Chee Eng; Draman, Che Rosle; Wan Ali, Wan Ahmad Syahril Rozli (John Wiley & Sons, Inc., 2015)
INTRODUCTION The pathology of renal failure results in the deterioration of multiple physiologic, biochemical, and biologic bodily functions. Haemodialysis (HD) is the main method of therapy of reducing the damages, up to some extent. KT/V has long been used to measure the adequacy of haemodialysis, despite its limitations. It is still up to now a very useful and easy tool to measure the adequacy of HD. Earlier studies have also shown that KT/V is related to morbidity and mortality. The current recommended target for dialysis adequacy in HD patients is a KT/V of ≥ 1.2. However this recommendation is mainly based on using data from Western population. Even though there are studies to indicate that adult haemodialysis Asian patients experience similar or better intermediate outcomes compared to the Caucasians and African Americans, there is sparse data on the impact of KT/V on patient outcome in the general Asian haemodialysis population.